Comparison between Continuous Thoracic Epidural and Paravertebral Blocks for Postoperative Analgesia in Patients Undergoing Thoracotomy: Systematic Review - Alberto de Pontes Jardim Júnior; Thomas Rolf Erdmann; Thiago Viçoso dos Santos; Guilherme Muriano Brunharo; Clovis Tadeu Bevilacqua Filho; Márcio Joaquim Losso; Getúlio R. de Oliveira Filho (Brazilian Journal of Anesthesiology, 2013)
Background and objective: : Thoracotomy is a procedure associated with postoperative severe pain. Epidural block (EB) is considered the gold standard for its control. Paravertebral block (PVB) is an option for the management of postoperative pain. The aim of this study was to evaluate by meta-analyses the effectiveness of continuous thoracic epidural and paravertebral blocks for pain management after thoracotomy and the incidence of adverse effects. Method: The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. We analyzed primary (postoperative pain at rest) and secondary outcomes (urinary retention, nausea, vomiting, hypotension). We estimated the weighted mean difference for continuous variables and odds ratios for categorical variables. Results: We included eight prospective, randomized, controlled studies. Meta-analysis showed no statistically signiﬁcant differences between the two techniques regarding the outcomes of postoperative pain at rest at four, eight, 12, 16, 20, 24, 36, and 48 hours. Incidence of urinary retention was higher in EP group (OR = 7.19, CI95 = 1.87 to 27.7). The occurrence of hypotension was higher in PVB group (OR = 10.28, 95 = 2.95 to 35.77). There was no statistically signiﬁcant difference between both groups regarding the outcome nausea/vomiting (OR = 3.00, CI95 = 0.49 to 18.45). Conclusion: There were no statistically signiﬁcant differences in pain relief after thoracotomy between EB and PVB. PVB showed a lower incidence of side effects with reduced frequency of urinary retention and hypotension. Keywords: Analgesia, Epidural, Anesthesia, Epidural, Nerve Block, Pain, Postoperative, Postoperative Complications, Thoracotomy